Characters in process in The Color Purple - Talif, Rosli; Sedehi, Kamelia Talebian (Elsevier, 2014)
Alice Walker's The Color Purple deals with the notion of sexism, racism and gender discrimination and their negative psychological effects on women's mind. In this novel, Walker criticizes all kinds of discriminations. The characters, especially the main female characters: Celie, Shug Avery, Sofia, and Squeak, do not have stable identity, but their identity is fluid and dependent on their own language and desires and other characters speech and emotions. The characters are under the influence of their own thoughts and emotions; moreover, other characters‟ desires and speech influence them too. Besides, the epistolary style of the novel helps the reader to comprehend the main characters fluid subjectivity. Different impressions prevent us from being confined to a single point of view. Therefore, being viewed from different perspectives, the main characters, as Kristeva holds, do not bear a solid and stable identity. In Julia Kriteva's view, the speaking subject does not have fixed identity but s/he is in the process of being. The speaking subject's identity is shaped through using language and interaction with other people. This paper intends to apply Kristeva's notion of subject in process to Walker's The Color Purple and indicate each character's opinion about discriminations and the way sexism, racism and gender discrimination influence their subjectivity.